Analysis of Financial Statements as a Tool to Measure the Financial Performance of Islamic Banks in Indonesia (An Empirical Study of Islamic Commercial Banks Registered with the Financial Services Authority for the Period 2021–2023) - Zulianty, Zahra Fatika; Witono, Banu (Majapahit Journal of Islamic Finance and Management, 2025)
This research is motivated by the dynamics of Indonesia’s economy in the post-COVID-19 pandemic period, which also impacted the performance of the banking sector, including Islamic banking, which plays a crucial role as an intermediary institution based on Sharia principles. The objective is to analyze the financial performance of Islamic Commercial Banks in Indonesia for the period 2021–2023 through profitability, liquidity, solvency, and activity ratios, as well as to identify differences in performance among banks. The method employed is descriptive quantitative using secondary data from annual financial statements published by the Financial Services Authority (OJK) and official bank websites, analyzed using ratio calculation, descriptive analysis, and the One-Way ANOVA test with SPSS 25. The results indicate significant variations in performance among banks, with low profitability, suboptimal asset utilization, and the need for improved operational efficiency, although liquidity and funding structure remain stable. The findings emphasize the necessity of asset optimization, improvement of intermediation strategies, and strengthening of operational management. The implications of this study point toward the standardization of financial reporting and the integration of non-financial indicators for a more comprehensive and sustainable evaluation of Islamic banking performance.